2017
DOI: 10.1186/s40657-017-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Do birds in flight respond to (ultra)violet lighting?

Abstract: Background: Concerns for bird collisions with wind turbines affect the deployment of onshore and offshore windpower plants. To avoid delays in consenting processes and to streamline the construction and operation phase, functional mitigation measures are required which efficiently reduces bird mortality. Vision is the primary sensory system in birds, which for a number of species also includes the ultraviolet spectrum. Many bird species that are known to collide with offshore wind turbines are sensitive in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Bostrom et al., 2016). Although ultraviolet paint (or other coloring) or lighting has also been proposed, these have so far shown limited efficacy (Hodos, 2003; May, Åström, Hamre, & Dahl, 2017; Young, Erickson, Strickland, Good, & Sernka, 2003). In addition, not all species are sensitive within the ultraviolet spectrum (Lind, Mitkus, Olsson, & Kelber, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Bostrom et al., 2016). Although ultraviolet paint (or other coloring) or lighting has also been proposed, these have so far shown limited efficacy (Hodos, 2003; May, Åström, Hamre, & Dahl, 2017; Young, Erickson, Strickland, Good, & Sernka, 2003). In addition, not all species are sensitive within the ultraviolet spectrum (Lind, Mitkus, Olsson, & Kelber, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly interesting because previous studies have suggested the use of these lights to reduce bird collisions. For instance, ultraviolet lights have been recommended to minimize collisions with wind turbines ( May et al, 2017 ); green lights, with offshore platforms ( Poot et al, 2008 ); and white lights, with communication towers ( Gehring, Kerlinger & Manville, 2009 ). However, all these studies were observational in nature (i.e., recording wild bird behavior/mortality around objects with different types of lighting) and did not control for many of the factors that could lead to misleading results (i.e., variations in individual identity, hunger levels across individuals, flying heights across trials, etc.…”
Section: Discussionmentioning
confidence: 99%
“…If lighting is employed as a means of minimizing bird collisions with human-made structures and vehicles through enhanced detection and avoidance, we must understand how the visual conspicuousness of lights affects choice behavior. This is important because of the variation in the type and degree of behavioral responses of birds to different wavelengths of light ( Gehring, Kerlinger & Manville, 2009 ; De Jong et al, 2015 ; May et al, 2017 ; Hunt, McClure & Allison, 2015 ). Our two-tiered methodological approach provides one way of tackling this complex problem, as behavioral responses to different suprathreshold visual signals can be highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…These Guidelines follow CSBI's definition of mitigation hierarchy. To note, there are alternative approaches to implementing the mitigation hierarchy to achieve the same result, such as that detailed in May (2017), which advocates a five-step approach tied to the decision gates for wind farm development: 1) avoid when planning, 2) minimise while designing, 3) reduce at construction, 4) compensate during operation, and 5) restore as part of decommissioning. avoid, minimise, restore and offset.…”
Section: Electricity Generationmentioning
confidence: 99%